Do employment subsidies reduce early apprenticeship dropout? - Jan Fries; Christian Göbel; Michael F. Maier (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
We evaluate the effect of the Apprenticeship Bonus, an employment subsidy programme, on early dropout of apprenticeship. Eligibility to the programme is restricted to school leavers who have actively searched for apprenticeship training to start immediately after leaving school, but were unsuccessful in finding a position. Our analysis is based on rich survey data that has been collected specifically for this study. Using this data, we describe the characteristics of school leavers who have searched for apprenticeship positions unsuccessfully directly leaving school and analyse the effect of the subsidy on the risk of apprenticeship dropout. Even though the subsidy provides strong incentives to prevent dropout, we do not find significant effects of the programme. Our finding suggests that financial incentives are not effective in increasing the probability to finish vocational in-firm training successfully.
urn:nbn:de:bsz:180-madoc-345634
Keywords: I21; J08; J38; 330; Apprenticeship; vocational training; subsidized employment; dropout